Development of Digital Puzzle Game-Based Learning Media to Improve Linguistic Intelligence in Early Childhood - Nur Fitriya Zulkarnain; Eva Selva Nirwana (STAI Hubbulwathan Duri, 2025)
Linguistic intelligence is crucial for children's early communication skills, enabling them to effectively understand and express thoughts, feelings, and needs. Digital games, accessible via Android and web platforms, offer an engaging way for children to enhance their linguistic abilities. This study aims to develop and evaluate digital puzzle game-based learning media to improve linguistic intelligence in young children. This research follows a Research and Development (RD) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The study involved 15 children as experiment participants, two lecturers as validators, one teacher as an effectiveness tester, and the researcher. Instruments used include expert validation sheets, questionnaires, and practicality test sheets. The developed digital puzzle game-based learning media was validated by experts, achieving 100% validity from material experts and 97.92% from media experts, indicating a